Emerging roles of β-cell mitochondria in type-2-diabetes. (February 2020) - Las, Guy; Oliveira, Marcus F.; Shirihai, Orian S.
Abstract: Type-2-Diabetes (T2D) is the most common metabolic disease in the world today. It erupts as a result of peripheral insulin resistance combined with hyperinsulinemia followed by suppression of insulin secretion from pancreatic β-cells. Mitochondria play a central role in β-cells by sensing glucose and also by mediating the suppression of insulin secretion in T2D. Here, we will summarize the evidence accumulated for the roles of β-cells mitochondria in T2D. We will present an updated view on how mitochondria in β-cells have been associated with T2D, from the genetic, bioenergetic, redox and structural points of view. The emerging picture is that mitochondrial structure and dysfunction directly contribute to β-cell function and in the pathogenesis of T2D.